1997
DOI: 10.1097/00004728-199711000-00022
|View full text |Cite
|
Sign up to set email alerts
|

The MR Appearance of Volume Overload in the Lower Extremities

Abstract: Subcutaneous tissue edema is the dominant feature of VO in the lower extremities. Perifascial fluid is common but does not necessarily distribute symmetrically. Muscle edema is relatively mild. These findings should aid in identifying VO as the potential cause of swelling in patients with swollen legs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Similar reticular patterns have been observed in patients with volume overload, e.g. cardiac failure or nephrotic syndrome (14), and in acute infectious cellulitis (15). It might be possible in most cases, however, to differentiate between the reticular pattern in volume overload patients and the honeycomb pattern in lymphedema patients, since the fat lobules in lymphedema are larger than in normal legs, partly as a result of fat neogenesis which is characteristic of lymphedema (10).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similar reticular patterns have been observed in patients with volume overload, e.g. cardiac failure or nephrotic syndrome (14), and in acute infectious cellulitis (15). It might be possible in most cases, however, to differentiate between the reticular pattern in volume overload patients and the honeycomb pattern in lymphedema patients, since the fat lobules in lymphedema are larger than in normal legs, partly as a result of fat neogenesis which is characteristic of lymphedema (10).…”
Section: Discussionsupporting
confidence: 68%
“…The dermal edematous thickening could be helpful in differentiating lymphedema from diseases with similar reticular subcutaneous features, e.g. in nephrotic syndrome and cardiac overload patients in whom dermal edema is not found (8, 14). However, such an assessment has to be made with caution since, in the present and other studies (8, 9), dermal edema has not been demonstrated in all lymphedema patients – the negative ones presumably being cases of clinical stage I or less severe stage II lymphedema.…”
Section: Discussionmentioning
confidence: 99%
“…MR-based measurements of local disruptions of tissue fluid distribution have proven clinical utility. 41,63,64 Our work extends this to measure systemic fluid depletion via localized measurement of tissue fluid distribution.…”
Section: Discussionmentioning
confidence: 78%
“…In addition to these volumetry-based studies, numerous MR studies also examined the morphological MR appearance of lymphedema or phlebedema in the lower extremity [26 -28]. Meler et al reported a marked subcutaneous, perifascicular and even intramuscular fluid accumulation, but only used morphological MR sequences in patients with fluid overload [29]. However, to our knowledge no previous study quantitatively investigated the influence of gravitational interstitial fluid accumulation in tendinous tissue in the lower extremity.…”
Section: Musculoskeletal System 1007mentioning
confidence: 99%